Immune checkpoint CD161/LLT1‐associated immunological landscape and diagnostic value in oral squamous cell carcinoma - Xinyang Hu; Yuexin Dong; Shixin Xie; Yuxian Song; Chenhang Yu; Yijia He; Zhiyong Wang; Qingang Hu; Yanhong Ni; Liang Ding (Wiley, 2024)
Abstract An active host adaptive response is characterized by the existence of programmed cell death protein 1 (PD‐1)+/IFN‐γ+ cytotoxic T cells and IFN‐γ‐induced PD‐L1+ tumor cells (TCs), which predicts high response rate to anti‐PD‐1/L1 therapy. Recently, CD161 and its ligand LLT1 (CLEC2D) have been identified as an emerging checkpoint for immunotherapy. Clarifying its heterogeneous clinical expression pattern and its immune landscape is a prerequisite for maximizing the response rate of CD161 blockade therapy in a specific population of oral squamous cell carcinoma (OSCC) patients. Here, we investigated the expression pattern of CD161/LLT1 and its association with major immunocytes (T cells, B cells, NK cells, and macrophages) by multiplex immunofluorescence, immunohistochemistry, and flow cytometry in 109 OSCC tissues and 102 peripheral blood samples. TCs showed higher LLT1 levels than tumor infiltrating lymphocytes (TILs), whereas CD161 was highly expressed in CD8+ T cells at the tumor front, which was decreased in paracancerous tissue. High expression of TC‐derived LLT1 (LLT1TC) conferred poor clinical outcomes, whereas higher CD161+ and LLT1+ TILs were associated with better prognosis. Meanwhile, patients with high LLT1TC showed a decreased ratio of CD8+/Foxp3+ T cells in situ, but CD161+ TILs correlated with more peripheral CD3+ T cells. Interestingly, treatment of OSCC patients with nivolumab (anti‐PD‐1) could restore tumoral CD161/LLT1 signal. Furthermore, an OSCC subgroup characterized by high LLT1+ TCs and low CD161+CD8+ T cells showed fewer peripheral T cells and a higher risk of lymph node metastasis, leading to a shorter 5‐year survival time (29%). More LLT1TC at the invasive front was another risk characteristic of exhausted T cells. In conclusion, in view of this heterogeneity, the LLT1/CD161 distribution pattern should be determined before CD161‐based immunotherapy.